IMPROVING ELEMENTARY SCHOOL STUDENTS’ SPEAKING SKILL ABILITY USING PASS BALL GAME - Ainul Duma Sari; Zul Amri (Journal of English Language Teaching, 2016)
Speaking skill is the main thing to be mastered as the language teaching need oral production result. However, speaking skill can’t be achieved easily as long as the use of inappropriate technique especially to the first formal school’s learner young learner. Thus, teacher needs to give interesting technique so students could achieve speaking ability without any obstacle. One of technique to teach speaking is the use of Pass Ball Game. This activity involves the most favourite of children toys; ball. Students will play with the ball in line with the performing speaking skill. As a result, students will consider that English language is easy to be mastered and interesting lesson.